2017
DOI: 10.1016/j.ccell.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Glycosylation in Cancer: A Novel Molecular Mechanism Controlling Metastasis

Abstract: Glycosylation alterations are involved in several steps of human cancer pathogenesis. In this issue of Cancer Cell, Agrawal et al. identified the glycosyltransferase FUT8 as a previously unrecognized mediator of melanoma metastasis, establishing core fucosylation as a potential therapeutic target for prevention and treatment of metastatic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 10 publications
1
109
0
Order By: Relevance
“…Cancer development and progression encompass major alterations in cell glycosylation, including incomplete synthesis of O ‐glycan structures, increased expression of branched N ‐glycans, expression of terminal sialylated glycans, and altered fucosylation. Reprinted from with permission.…”
Section: Aberrant Glycan Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer development and progression encompass major alterations in cell glycosylation, including incomplete synthesis of O ‐glycan structures, increased expression of branched N ‐glycans, expression of terminal sialylated glycans, and altered fucosylation. Reprinted from with permission.…”
Section: Aberrant Glycan Expressionmentioning
confidence: 99%
“…Glycans are also determining the interaction between cancer cells and tumor environment, especially the ECM. Glycan alternations are responsible for tumor progression because of modulation of oncogenic receptors, proteoglycans, and adhesion proteins .…”
Section: Analytical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered N‐glycosylation is catalyzed by the specificity of glycosyltransferases, including FUTs, N‐acetylglucosaminyltransferases, galactosyltransferases, and sialyltransferases in the Golgi apparatus . Previous studies have shown that the expression levels of N‐glycan branching enzymes (such as α‐1,6‐mannosyl‐glycoprotein β‐1,2‐ N ‐acetylglucosaminyltransferase and α‐1,3‐mannosyl‐glycoprotein 4‐β‐ N ‐acetylglucosaminyltransferase A), sialyltransferases (such as ST6 β‐galactoside α‐2,6‐sialyltransferase [ST6GAL]1 and ST6GAL2) and β1,6‐branched N‐linked oligosaccharides, are increased in melanoma cells, and these increases in expression contribute to the invasive and metastatic potential of melanoma cells …”
Section: Introductionmentioning
confidence: 99%
“…9 Previous studies have shown that the expression levels of N-glycan branching enzymes (such as α-1,6-mannosyl-glycoprotein β-1,2-N-acetylglucosaminyltransferase and α-1,3-mannosyl-glycoprotein 4-β-N-acetylglucosaminyltransferase A), sialyltransferases (such as ST6 β-galactoside α-2,6-sialyltransferase [ST6GAL]1 and ST6GAL2) and β1,6-branched N-linked oligosaccharides, are increased in melanoma cells, and these increases in expression contribute to the invasive and metastatic potential of melanoma cells. 10,11 FUT enzymes serve an important role in the synthesis of fucosylated glycans. FUT1 and FUT2 catalyze the transfer of a fucose residue in an α-1,2-linkage to the terminal galactose (Gal) residue in N-glycans.…”
Section: Introductionmentioning
confidence: 99%